Regional Government Politics in Indonesia: A Critical Legal Studies Perspective - Furqon, Eki; Karsa, Pipih Ludia; Oktavianus, Afriman; Arifianto, Rizky (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
The legal politics of regional government in Indonesia is intrinsically tied to regional autonomy, a constitutional pillar of governance. This research examines the causal relationship between the political and legal subsystems in implementing regional autonomy. Using a normative juridical approach, it highlights how legal policies—whether through new laws or amendments—reflect political dynamics. Grounded in the Critical Legal Studies (CLS) perspective, the study critiques the notion of legal neutrality, arguing that positive law, both in its formulation and application, is deeply embedded in political interests. This interdependence underscores how laws on regional autonomy, including those under Law Number 23 of 2014, are shaped by societal and political contexts. The research contributes by revealing how the CLS framework explains the fluid dynamics of regional autonomy, emphasizing the interplay between law and politics in shaping governance. It offers critical insights into achieving balanced autonomy within Indonesia’s unitary state framework.